2018
DOI: 10.1002/2017jg004063
|View full text |Cite
|
Sign up to set email alerts
|

No Correlation Between Atmospheric Dust and Surface Ocean Chlorophyll‐a in the Oligotrophic Gulf of Aqaba, Northern Red Sea

Abstract: High‐resolution records of daily surface chlorophyll‐a (chl‐a) concentrations and hourly atmospheric dust concentrations in the Gulf of Aqaba, northern Red Sea, are compared between 2012 and 2016 in order to examine the interplay between atmospheric dust input and surface productivity in this subtropic, nutrient‐poor marine ecosystem. Given that lags of days to weeks may occur between the dust input and phytoplankton response, and because of potential biases associated with differences in the sampling resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 61 publications
1
25
1
Order By: Relevance
“…Our results confirm the presence of high loads of prokaryote and VLPs in dust suspended in the atmosphere over the Red Sea. Recent assessments of the chemical composition of dust in the northern Red Sea region report dust loads ranging from 20 to 30 μg m −3 (Torfstein et al, 2017; Torfstein and Kienast, 2018), which are 22-fold lower than those reported here. However, comparison of our results with other related studies is precluded by the absence of studies the quantifying the abundance of aerosol prokaryotes and VLPs particles in the Red Sea or even in the Mediterranean Sea, through which some of the air masses delivering microbes to the Red Sea transit.…”
Section: Discussioncontrasting
confidence: 75%
“…Our results confirm the presence of high loads of prokaryote and VLPs in dust suspended in the atmosphere over the Red Sea. Recent assessments of the chemical composition of dust in the northern Red Sea region report dust loads ranging from 20 to 30 μg m −3 (Torfstein et al, 2017; Torfstein and Kienast, 2018), which are 22-fold lower than those reported here. However, comparison of our results with other related studies is precluded by the absence of studies the quantifying the abundance of aerosol prokaryotes and VLPs particles in the Red Sea or even in the Mediterranean Sea, through which some of the air masses delivering microbes to the Red Sea transit.…”
Section: Discussioncontrasting
confidence: 75%
“…It is important to reiterate that the above-described structure of the 2016 event is largely consistent with the sequence of March–April 2015, indicating the observed patterns are systematic, rather than reflecting sampling biases or random signals within natural variability. In addition, previous comparisons of Chl- a surface concentrations between monthly resolved sampling in the deep GOA ( station A ) and daily resolved sampling at the IUI shore, display strong consistency 42 . Thus, the combined evidence suggests a systematic driving mechanism rather than chaotic seawater circulation patterns (e.g., eddies or patchiness 43 ) is the fundamental modulator of the observed daily timescale variability of PF fluxes.…”
Section: Discussionmentioning
confidence: 72%
“…Chl- a concentrations and sea surface temperatures (SST) were measured daily by the Israel National Monitoring Program (NMP) ( https://www.iui-eilat.ac.il/Research/NMPmeteodata.aspx ) at the pier of the Interuniversity Institute (IUI) for Marine Sciences at Eilat (Supplementary Fig. S1 ) and have been shown to be consistent with coeval values at station A 42 . Additionally, the NMP measured monthly profiles of water column temperatures, salinity, Chl- a concentrations, nutrient contents (TON, NO 2 − , NO 3 − , PO 4 3− , Si(OH) 4 )) at Station A (29° 28.22′ N, 34° 55.50′ E).…”
Section: Methodsmentioning
confidence: 99%
“…Another source of nitrogen which could significantly affect this region is atmospheric deposition, as the Gulf of Aqaba receives considerable dust input from the surrounding deserts. Recently, it has been shown that atmospheric dust input does not correlate with chlorophyll variability in surface waters of the Gulf of Aqaba (Torfstein and Kienast, 2018). In contrast, a previous study suggested that atmospheric deposition of nitrogen could support over 10 % of surface primary production in the region, based on measurements of local aerosol composition and a dust deposition model (Chen et al, 2007).…”
Section: Limitations and Uncertaintiesmentioning
confidence: 94%